Medium optimization for 5'-phosphodiesterase production from Penicillium citrinum using response surface methodology - Shi, Lu-E (Array, 2007)
Summary: Medium optimization for 5'-phosphodiesterase production from Penicillium citrinum was studied by applying one-factor-at-a-time method, orthogonal array method and response surface methodology in this paper. The one-factor-at-a-time method was used to study the effects of carbon, nitrogen, phosphorus and metal ion sources on 5'-phosphodiesterase production. Among various carbon and nitrogen sources used, glucose and peptone were the most suitable substances for 5'-phosphodiesterase production, respectively. Subsequently, the concentrations of glucose, peptone, groundnut meal, Zn2+ and KH2PO4 were optimized using the orthogonal array method. Response surface methodology was also applied for medium optimization. Glucose concentration (X1), peptone concentration (X2) and groundnut meal (X3) were selected as the independent variables. Results showed that the regression models adequately explained the data variation and represented the actual relationships between the parameters and responses. The optimum conditions were glucose at a fraction of 6.5 %, peptone at a fraction of 0.45 % and groundnut meal at a fraction of 1.0 %. Maximum enzyme activity was 353 U/mL under the optimum conditions